Robust Ni/Dendritic Fibrous SBA-15 (Ni/DFSBA-15) For Methane Dry Reforming: Effect of Ni Loadings - Chong, C. C.; Bukhari, S. N.; Cheng, Y. W.; Setiabudi, H. D.; Jalil, A. A.; Phalakornkule, C. (Elsevier, 2019)
A series of spherical mesoporous Ni/Dendritic Fibrous SBA-15 (Ni/DFSBA-15) catalysts with different Ni loadings (3-15 wt.%) were successfully synthesized and catalytically investigated by methane dry reforming. The XRD and Raman analyses indicated the structural stability of DFSBA-15 regardless of the Ni loading quantity, and the NiO nanocrystalline size increased with increasing Ni loading. The BET analysis showed the surface area of the catalysts decreased upon increment in Ni loading. Meanwhile, the TEM images revealed the distribution of Ni particles over the spherical shape DFSBA-15, with the most homogeneous dispersion was shown by 10Ni/DFSBA15, while Ni agglomeration was observed for 15Ni/DFSBA-15. The optimal catalytic performance and stability was achieved by 10Ni/DFSBA-15 (